"Can I Alter the Statement?" – Considering Holocaust Education as a Catalyst for Civic Education in Jewish Day Schools. Issue 3 (3rd July 2022) - Katz, Meredith
ABSTRACT: This study investigates ideas about the messages of the Holocaust understood by middle school students in Jewish day schools. Findings explore the conceptualizations students have of the Holocaust as a particular Jewish experience, and in what ways they apply its lessons both particularly and universally. Students in two North American Jewish day schools participated in a fall 2017 Holocaust education unit. Most were able to connect to the particular history of the Holocaust and to engage with universal messages. Their responses suggest a need and opportunity to frame Holocaust education more explicitly in the context of democratic civic education.